True emotions - Salmela, Mikko, 1967- (Consciousness & emotion book series, 2014)
True Emotions discusses several key problems in emotion research. The question about the true nature of emotions focuses on the role of cognition in human emotions at different levels of analysis: functional role, types of processes and representations, and neural implementation. Truth to the self, or authenticity, has two meanings, psychological and normative, where the latter is analyzed as coherence between the evaluative content of an emotion and the subject's internally justified beliefs and values. Truth to the world is argued to be a matter of correct evaluative representation of the emotional object on the one hand, and the existence of the object, or the actuality or accurate probability of the represented situation on the other hand. Finally, authenticity and truth are applied to analyses of the authenticity of occupational emotions and the constitution of sentimental values, respectively.